Predictors and survival for pathologic tumor response grade in borderline resectable and locally advanced pancreatic cancer treated with induction chemotherapy and neoadjuvant stereotactic body radiotherapy. (4th March 2017) - Mellon, Eric A.; Jin, William H.; Frakes, Jessica M.; Centeno, Barbara A.; Strom, Tobin J.; Springett, Gregory M.; Malafa, Mokenge P.; Shridhar, Ravi; Hodul, Pamela J.; Hoffe, Sarah E.
Abstract: Background: Neoadjuvant therapy response correlates with survival in multiple gastrointestinal malignancies. To potentially augment neoadjuvant response for pancreas adenocarcinoma, we intensified treatment with stereotactic body radiotherapy (SBRT) following multi-agent chemotherapy. Using this regimen, we analyzed whether the College of American Pathology (CAP) tumor regression grade (TRG) at pancreatectomy correlated with established response biomarkers and survival. Materials and methods: We identified borderline resectable (BRPC) and locally advanced (LAPC) pancreatic cancer patients treated according to our institutional clinical pathway who underwent surgical resection with reported TRG (n = 81, median follow-up after surgery 24.2 months). Patients had baseline CA19-9, computed tomography (CT), endoscopic ultrasound, and FDG positron emission tomography (PET)/CT then underwent multi-agent chemotherapy (79% with three cycles of gemcitabine, docetaxel and capecitabine) followed by 5-fraction SBRT. They then underwent restaging CT, PET/CT and CA19-9. Overall (OS) and progression-free (PFS) survival were estimated and compared by Kaplan–Meier and log-rank methods. Univariate ordinal logistic regression correlated TRG with baseline, restaging and change in CA19-9 and the PET maximum standardized uptake value (SUVmax). Results: Restaging level and decrease in CA19-9 correlated with improved TRG (p = .02 for both) as did restaging SUVmax (p < .01), yet there was no TRG correlation with decrease in SUVmax (p = .10) or CT response (p = .30). The TRG groups had similar OS and PFS except the TRG 0 (complete response) group. Compared to partial response levels (TRG 1-3, median OS 33.9 months, median PFS 13.0 months), the six (7%) patients with TRG 0 had no deaths (p = .05) and only one progression (p = .03). A group of 10 (12%) TRG 1 patients with only residual isolated tumor cells had similar outcomes to the other TRG 1-3 patients. Conclusion: Pre-operative PET-CT and CA19-9 response correlate with histopathologic tumor regression. Patients with complete pathologic response have superior outcomes, suggesting a rationale for intensification and personalization of neoadjuvant therapy in BRPC and LAPC.